Mobile user location prediction: genetic algorithm-based approach - Mantoro, Teddy; Muataz, Zubaidah; Ayu, Media Anugerah (2010)
Context histories, especially when recorded over a long term, offer a wide range of possibilities to enhance the services provided by ubiquitous computing system application. These possibilities include inferring of current and past user location, and selection of devices. However, the prediction of future context based on the recorded past locations is often conceived as the ultimate challenge in exploiting the whole of context histories. This paper presents a prediction of user location using genetic algorithm and based location history in finding a number of solutions of possible location when applied to recorded context histories, framework is presented and the result are discussed.